Arteriovenous Fistula Is a Rare but Significant Finding After Endovenous Thermal Ablation. Issue 3 (September 2019) - Kelly, Donna M.; Sanford, Deborah; Stoughton, Julianne
Endovenous thermal ablation (EVTA) has become the mainstay of treatment for symptomatic varicose veins in the setting of saphenous vein insufficiency. We observed 5 iatrogenic arteriovenous fistulas (AVFs) following thermal ablation of the great saphenous vein (GSV). Postprocedure duplex ultrasound (DUS) results were analyzed for the presence of AVF in any location along or adjacent to the treated saphenous veins. Cases were prospectively followed. English literature was reviewed for any other published reports of AVF after EVTA. Data were compiled using our 5 cases, 2 cases were shared with us by colleagues and 20 cases were reported in the literature. Our center has performed more than 4000 (4155) cases of EVTA over the past 15 years. Five cases of AVFs were detected, 3 were found in asymptomatic patients during routine post-EVTA surveillance. The additional 2 cases presented with signs or symptoms which prompted a DUS after ablation. Including cases in the literature, we were able to identify 2 different types of AVFs. The first type of AVF was demonstrated in 13 cases where the AVF occurred along the treated vein. All of these cases involved ablation of the GSV and 90% of these showed signs of recanalization. The second type of AVF was seen in 14 additional cases where the AVF involved a vein segment adjacent to or remote from the ablated vein. The second type occurred in the GSV in 5 cases, external iliac vein (EIV) in 3 cases, and in the popliteal vein in 5 cases. There is 1 reported case of AVF involving the sural artery after perforator vein EVTA. Three of the type 1 cases were followed and spontaneously resolved; 3 of the type 1 cases were treated with surgical ligation with unreported outcomes. Seven cases did not report any follow-up information. Seven of the type 2 cases were treated, and had spontaneous resolution and 7 were not treated. The follow-up on these cases ranged from 1 month to 6 years. Thermal ablation can result in AVF either along the length of the treated vein or adjacent to the area of ablation. Further study would help elucidate the cause and treatment algorithms.